AUTHORITY AND JURIDICAL REVIEW OF THE DECISION OF THE ELECTION ORGANIZATION COUNCIL (DKPP) IN PRODUCING DEMOCRATIC ELECTIONS IN INDONESIA (Analysis of Law Number 7 of 2017 Concerning General Elections) - Perdana, Andre Pebrian; Fatihillah, Teuku M Naufal (Progressive Law Review, 2021)
ABSTRACT The Election Organizer Honorary Council (DKPP) is one of the triumvirate of election organizers in Indonesia. Election law politics in Indonesia is in a status a quo giving DKPP such coercive authority regarding enforcement of the code of ethics. However, so coercive of the powers that DKPP actually raises fundamental questions, namely those related to: 1. How does the code of ethics correlate with the implementation of democratic elections in Indonesia? 2. How does DKPP's authority correlate with the creation of democratic elections? This research is a juridical study that uses a statute approach, a conceptual approach, and a case approach to address these problems. Based on this research, it is found that the Election Code of Ethics is correlated as a manifestation of the organizing rules that are formed together in order to create honest and fair elections in order to create substantially democratic elections, not just procedural ones. In addition, it was found that the coercive authority of DKPP is to ensure that Election Administrators comply with the Code of Ethics, which is the rules for administering elections. When DKPP does not have this coercive authority, it will make DKPP appear to be a blunt sword which will lead to elections that do not reflect substantive democracy. Keywords: democracy, Honorary Council for Election Implementation.